Dentistry’s colaboration on breastfeeding encouragement during interprofessional action in Combu Island, in Amazon: PET-Health/UFPA experience report (Research, Society and Development, 2023)
Objective: Integrality is a concept that must be applied to all areas of health care, considering that dentistry has great importance in this process. This study’s objective is to relate the experience of a group of students and tutors from courses as Dentistry, Medicine, Nutrition and Occupational Therapy in an interprofessional health action developed with a group of women from PROAME, in Combu Island, during World Breastfeeding Week, besides elucidating dentistry collaboration in full care during puerperium and breastfeeding. Methodology: It is a descriptive study, experience report type, done by the group of PET-Heath/Interprofissionality. Pregnant, puerperal and breastfeeding women from Combu Island were invited by the health team to an event with workshops, talk circles and interactive activies about the benefits of breastfeeding.  During the event, there was great interaction between diferente health areas, correlating breastfeeding nutritional benefits along with the development of the stomatognathic complex and dental arches, as much as immunological, emotional and motor benefits. Conclusion: It was possible to obtain horizontal communication between community women and health team, promoting, then, exchange experiences and knowledges and nurture humanized strategies in Primary Health Care.